Uma visão sistemática sobre fitase em dietas para tilápias - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2024)
Ingredients of vegeteble source used in fish’ feed contain antinutricional factors in your composition, such as the phytato. This factor is responsable for reducing the digestibility of the phosphorus, energy and other nutrientes, such as the protein, the starch and minerals. The phytase came as a tool to catalyse the phytato’s hydrolysis and improve the biodisponibility of these unavailabe nutrientes. Because of the variety of phytases and inclusion levels existing commercially, as well of the diversity of results to be found in the literature, the meta-analysis can be used as a way to reunite the results published among the years. This paper aims to avaluate, using meta-analysis combined with systematic analysis, the effects of the addition of phytase over the performance, the digestibility of the nutrients and the energy, furthermore, the environmental aspects and impacts in tilapias’ diets. The criteria established for the selection of the articles were experiments with the use of phytase in tilapias’ diets and the effects in performance, nutrientes digestibility and environmental response. Hereby, there were 40 articles complied, between the years of 2000 to 2023, totalizing 269 treatments. The data analysis was explored by scatter plots, individual variation, variance and forest plot. The variance analysis indicated that the phytase improved the feed conversion ratio (FCR) (P = 0,014) and the apparent digestibility coefficient of phosphorus (ADC P) (P = 0,00) of fingerlings and weight gain (WG) (P = 0,015), FCR (P= 0,045) and ADC P (P = 0,029) of tilapias’ juveniles. The scatter plots and individual variation plots corroborate with the results. The phytase was responsable for reproducing the same results in diets with P restrition when compared with diets with inclusion of inorganic P. As the inclusion levels, levels between 1500 a 2000 FTU/kg are enough to create positive results in performance and digestibility. The inclusion of phytase is efficient in improving WG, FCR and reducing the levels of total feed consumption of tilapias’ fingerlings and juveniles, as well as improving the ADC P of diets with ingredientes from vegetable source. In diets with P restrition, the phytase will improve digestibility and performance parameters, replacing the addition of P in inorganic form, reducing the production cost and the environmental impacts caused by the liberation of this mineral to the external environment.
Keywords: Peixes; fitato; fósforo; meta-nálise; fator antinutricional; Fish; phyato; phosphorus; meta-analysis; antinutricional factors; CNPQ::CIENCIAS AGRARIAS::ZOOTECNIA